Relationship between environmental variables and Marine Nematode densities in Teluk Awar, Sarawak Malaysia - Cheng, Ann Chen; Shabdin, M.L.; Mohd Rosli, Norliana (Monograph Aquatic Science Colloqium, 2010)
A pilot study was carried out in Sarawak on the community structure of free-living marine nematode. The aim of this study was to determine the horizontal distribution of marine nematode associated with abiotic and biotic environmental factors. One-way ANOVA showed significant differences in the environmental variables (salinity, pH, dissolved oxygen, temperature, total organic matter) for both study transects. Chlrophyll a only showed significant difference in transsect A.